Study of phytoproteases stability in aqueous-organic biphasic systems using linear free energy relationships - Barberis, Sonia (2006)
In this paper we study the effect of different water-immiscible organic solvents (benzene, toluene, 1-butanol, 1-octanol, dichloroethane, dichloromethane, diethyl ether, hexane, chlorobenzene, acetophenone, n-dodecane, trichloroethylene, ethyl acetate) on the stability (residual caseinolytic activity after 4 h) of soluble phytoproteases, such as araujiain, funastrain and papain in aqueous-organic biphasic systems. Besides, the effect of organic solvents on enzymatic catalysis was quantitatively studied by means of linear free energy relationships (LFERs). The organic solvents were characterized by several physicochemical properties, and multiple linear regression analysis (MLRA) together with non-linear regression were the methods used to search the relationships between the residual caseinolytic activity data and several physicochemical parameters. Those enzymes show much greater activity and stability in some biphasic media than in water. On the other hand, all developed correlations represented highly significant LFERs models and showed that non-specific polar and hydrophobic factors are of prime and approximately equal importance for the biocatalytic activity of araujiain, funastrain and papain in the studied biphasic systems, while the specific polar interactions are of little importance for activity. The results suggested that araujiain, funastrain and papain do not suffer unfolding in the studied biphasic media and they are able to retain their native or native-like configurations, though with altered characteristics or properties. This fact was demonstrated by means of a comparative FTIR spectroscopy study in both, buffer and biphasic media, for each studied enzyme.